Civil Society Organizations and the Development of Nigeria’s Foreign Policy - Philip U, Afaha; Ugonna, Obi-Emeruwa (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Recent studies have depicted Nigeria’s foreign policy as constantly in a state of flux due to the internal and external dynamics inherent in any given administration or regime. In the case of Nigeria, the formation of Nigeria’s foreign policy has gone through 14 different administrations in the past 53 years, out of which 35 years were under military regimes. To this end, Nigeria has very strong civil society organizations, which have had constructive influences in the country's foreign policies. They have acted as important forces and platforms for creating and recreating stability towards the consolidation of democracy in Nigeria. They have nonetheless become the basis for a durable new political authority, regardless of the plethora of problems besetting them generally. It is against this background that this paper seeks to discuss the impacts of civil society organizations on the development of Nigeria foreign policy.